Engaging globalization : the poor, Christian mission, and our hyperconnected world - Myers, Bryant L. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2017)
Globalization is speeding up our world, extending our relationships globally and bringing us closer together in positive and not-so-positive ways. The church and many Christians, however, remain largely unaware of its seductive power, resulting in a failure of vision for mission in today's world. This up-to-date resource by a veteran leader in global development work with World Vision orients readers to the history of globalization and to a Christian theological perspective on it, explores concrete realities by focusing on global poverty, and helps readers reimagine Christian mission in ways that announce the truly good news of Christ and God's kingdom. Diagrams and sidebars that incorporate the voices of global partners are included. This is the second book in a new series that reframes missiological themes and studies for students using/featuring the common theme of mission as partnership with Christians.
Section 1: Setting the Stage. 1. Introduction and the Path Forward -- 2. Twin Foundations. Theological Affirmations -- Complex Adaptive Social Systems -- Questions for Discussion -- Section 2: Introducing Globalization. 3. Understanding Globalization. The Problem of Definitions -- Globalization from Below -- The Dark Side of Globalization -- The Dynamic Domains of Globalization -- 4. The Ambiguities of Globalization. The Emergent Nature of Globalization -- Globalization's Unresolved Issues of Concern -- The Challenge to the Church in Mission -- Section 3: The Two Eras of Globalization. 5. The First Era of Globalization: Going Global by Migration, Conquest and Mission. The First Era -- The Transformation of Britain -- 6. The Second Era of Globalization: Globally Connected and Closer Together. The Second Era -- Globalization I: 1800-1914 -- The Great Disruption: 1914-89 -- Globalization II: 1989 to Today -- Section 4: The Impact of Globalization. 7. The Impact of Two Hundred Years of Globalization. Economic Growth -- Technological Change -- People Are Moving -- Better Human Lives -- Culture and People Change -- 8. Assessing the Second Era of Globalization. What Happened to the Poor? -- Differing Perspectives on Globalization -- The Last Two Hundred Years in a Nutshell -- Section 5: Globalization and the Poor. 9. Globalization's Response to Poverty. The State of the Poor Today -- The Global Response to the Poor -- 10. Contemporary Thinking on Development. Global Proposals for Poverty Eradication -- Recent Insights -- Faith and Development -- Section 6: Globalization and the Church. 11. Globalization and World Christianity. Two Preliminaries -- Christianity: An Enduring Globalism -- The Globalism of World Christianity -- The Changing Shape of the Christian Church -- The Frontiers of Mission Today -- 12. The Theological Limitations of Globalization. A Flawed Anthropology -- The Problem of Power -- The Relegation of Morality and Ethics -- The Missing Moral Ecology of Globalization -- 13. The Christian Engagement with Globalization. A Protestant Contribution / Max Stackhouse -- A Roman Catholic Contribution / Daniel Groody -- Changing Culture / James Davison Hunter -- The Decisive Importance of Prayer -- 14. The Missiological Challenge of Globalization. The Mission Field Has Changed -- A Different Kind of Missionary -- Discipleship Formation and Spiritual Disciplines -- Recovering the Good News in the Good News -- Recovering Our Confidence -- Are We Up to the Task?.
Includes bibliographical references (pages 259-275) and index.
Keywords: Globalization -- Religious aspects -- Christianity; Poverty -- Religious aspects -- Christianity; Missions